KAJIAN DESAIN GRAFIS VERNAKULAR, ADAKAH PELUANG DILUAR TIPOGRAFI VERNAKULAR? - Tjipto Rahardjo, Sudjadi; Marianto, Martinus Dwi (AKSA: Jurnal Desain Komunikasi Visual, 2025)
Visual cultural artifacts in Indonesia are abundant and spread throughout the region. These objects are visual riches that have not been widely studied. From visual culture researchers who are interested in local graphic design, what is called vernacular graphic design emerged. This research was conducted using a qualitative method of literature study to reveal a basic understanding of visual culture, vernacular design and vernacular graphic design. From the literature that has been collected, it turns out that the study of vernacular graphic design focuses on vernacular typography. There has been no study of vernacular illustration or photography, vernacular color composition and vernacular layout or further on the concept of vernacular design according to its creator. This gap is an opportunity for visual culture researchers to dig deeper into the concept of non-typographic vernacular graphic design elements.